ANALYSIS OF LAND PARKING INVESTMENT CASE STUDY IN ROAD R. SUPRAPTO PURWODADI CITY GROBOGAN DISTRICT - Heri Sulistiyono; Nina Anindyawati (UNISSULA Semarang, 2018)
ABSTRACTPopulation growth and growth of economic sector, causing high level of population mobility or high level of travel. Increased vehicle travel that is not followed by an increase in the quality and quantity of adequate transport infrastructure can lead to an imbalance between greater travel demands compared to the availability of existing transport infrastructure . Based on the above background, the existence of economic growth in Purwodadi City thus increasing the purchasing power and mobility of the population so that the density on the Road. R. Suprapto which is the main road or vein of Purwodadi City so that parking problem in Jalan R. Suprapto need to get serious attention. This study aims to determine the calculation of profit and loss for parking investment land. In detail the purpose of the study can be mentioned as follows: To know the parking area needed to fulfill the need. To know the pattern of parking arrangement that fit the optimal needs . To improve management of parking management in the study location . To find out the feasibility of investment of parking facility in the location of study. Data analysis performed include analysis of parking facility characteristics, parking forecasting analysis analysis and financial feasibility analysis of parking building development. as for the analysis technique using: Characteristic Analysis of Parking Facility and Financial Feasibility Analysis of Parking Building Development. Based on the evaluation of the financial feasibility parameters of the parking lot development project can be obtained the following results: Based on the feasibility analysis of the project, the construction of the parker is financially feasible to run. The construction of a parking space on Jalan R Suprapto Kota Purwodadi has economic and social benefits for the people of Grobogan Regency, especially in the region. Break Even Point (BEP) Construction of parking spaces on Jalan R Suprapto Kota Purwodadi is 3.49 or BEP occurs in the 3rd and 3rd months of the 3rd day. Keywords : Parking Feasibility Analysis, NPV, IRR, BCR, Road Section R Suprapto